The Culture Dish Surface Influences the Phenotype and Dissociation Strategy in Distinct Mouse Macrophage Populations - Song, Qiaoling; Zhang, Yazhuo; Zhou, Mingming; Xu, Yuting; Zhang, Qianyue; Wu, Lihong; Liu, Shan; Zhang, Minghui; Zhang, Lei; Wu, Zhihua; Peng, Weixun; Liu, Xutao; et al. (Frontiers in Immunology, 2022)
The nature of the culture dish surface and the technique used to detach adherent cells could very likely influence the cell viability and cell membrane protein integrity of harvested macrophages. Several previous studies assessed the detachment efficacies of enzymatic and non-enzymatic methods for harvesting the single cell suspensions of macrophages, but a comprehensive study assessing different dissociation methods and culture conditions for detaching functionally different macrophage populations has not yet been reported. In this study, via the well-established GM-CSF and M-CSF differentiated bone marrow derived macrophage models (GM-BMDMs and M-BMDMs), we compared four commonly used enzymatic (trypsin and accutase) and non-enzymatic (PBS and EDTA) dissociation methods along with necessary mechanical detaching steps (scraping and pipetting) to evaluate the viable cell recovery and cell surface marker integrality of GM-BMDMs and M-BMDMs cultured on standard cell culture dish (TC dish), or on culture dish (noTC dish) that was not conditioned to enhance adherence. The data showed that accutase yielded a better recovery of viable cells comparing with PBS and EDTA, especially for tightly adherent GM-BMDMs on TC dishes, with a relatively higher level of detected cell membrane marker F4/80 than trypsin. An additional gradient centrifugation-based dead cell removal approach could increase the proportion of viable cells for TC cultured GM-BMDMs after accutase dissociation. Furthermore, transcriptome analysis was performed to evaluate the putative influence of culture dishes. At steady state, BMDMs cultured on noTC dishes exhibited more proinflammatory gene expression signatures (e.g. IL6, CXCL2 and ILlβ) and functions (e.g. TNF and IL17 signaling pathways). Similar inflammatory responses were observed upon LPS challenge regardless of culture conditions and differentiation factors. However, in LPS treated samples, the difference of gene expression patterns, signaling pathways and molecular functions between TC and noTC cultured BMDMs were largely dependent on the types of growth factors (M-CSF and GM-CSF). This observation might provide valuable information for in vitro macrophage studies.